(untitled) (Academia Science Repository, 2023)
The author covers important problems of medical, psychological and pedagogical rehabilitation of children, which had undergone such surgery. The necessity of cooperation between doctors, psychologists, deaf-and-dumb pedagogues and the child’s family in order to achieve a successful restoration of the lost skills or to form new ones: perception of sound, speaking skills, social adoptation is being stressed.